Fragilidade e fatores associados à polifarmácia em pessoas idosas residentes em contextos de vulnerabilidade social: um estudo de método misto - Oliveira, Claudete de (2024)
In the aging process, there is a continuous decline of morphophysiological systems, which promotes changes in homeostatic balance, especially in the pharmacokinetics and pharmacodynamics of drugs in the aging body. Many elderly people use five or more drugs, constituting polypharmacy. Judicious prescription prevents drug interaction, adverse reactions, iatrogenic cascade and use of potentially inappropriate drugs for the elderly. This study aimed to analyze the relationships between sociodemographic characteristics and frailty, cognition and depression with the use of polypharmacy and sequentially analyze perceptions about the use of the prescribed medication and identify potentially inappropriate drugs, drug interactions and concomitant self-medication, in elderly people living in regions of social vulnerability. This was an exploratory, descriptive, cross-sectional study using a mixed method. For the development of the quantitative study, an existing database was used, with 238 elderly, qualitative data were collected through semi-structured interviews. The database used was derived from the following instruments: sociodemographic interview, Fried Frailty Scale, Mini-mental State Examination and Geriatric Depression Scale. All ethical procedures for research with human beings were observed. For the analysis of quantitative data, descriptive statistics were used, and the Shapiro-Wilks tests with p-value <0.05, the TStudent and Wald’s Chi-Square. For multivariate logistic regression, the Forward model was used, plus the Odds Ratio (OR) with the 95% confidence interval. For the qualitative data, Bardin’s content analysis was used and the interpretation was based on historical and dialectical materialism. The mean age of the participants with polypharmacy was 72.5 years. Drug consumption is higher among women (OR: 1.868 - 95%CI 1.052 - 3.316). The relationship between frailty and polypharmacy was significant (p-value <0.001), pre-frail (OR: 5.626 - 95%CI 2.038 - 15.531), fragile (OR: 12.083 - 95%CI 3.912 - 37.319), being higher among women. Polypharmacy predisposes to the consumption of potentially inappropriate drugs for the elderly and drug interaction. It was identified that the elderly person, manages self-care and care (a) partner (a) in the family, there is a high consumption of medicines and polypharmacy. It is concluded that pre-fragile and fragile women are more likely to use polypharmacy, which in combination with the progressive physiological decline, advancing age, chronicity of diseases, compromises the multimorbidity situation, and potentiates negative outcomes and health problems of the elderly.